A genome‐scale analysis of mRNAs targeting to plant mitochondria: upstream AUGs in 5' untranslated regions reduce mitochondrial association. (20th November 2017) - Vincent, Timothée; Vingadassalon, Audrey; Ubrig, Elodie; Azeredo, Kevin; Srour, Ola; Cognat, Valérie; Graindorge, Stéfanie; Salinas, Thalia; Maréchal‐Drouard, Laurence; Duchêne, Anne‐Marie
Summary: Intracellular sorting of mRNAs is an essential process for regulating gene expression and protein localization. Most mitochondrial proteins are nuclear‐encoded and imported into the mitochondria through post‐translational or co‐translational processes. In the latter case, mRNAs are found to be enriched in the vicinity of mitochondria. A genome‐scale analysis of mRNAs associated with mitochondria has been performed to determine plant cytosolic mRNAs targeted to the mitochondrial surface. Many messengers encoding mitochondrial proteins were found associated with mitochondria. These mRNAs correspond to particular functions and complexes, such as respiration or mitoribosomes, which indicates a coordinated control of mRNA localization within metabolic pathways. In addition, upstream AUGs in 5' untranslated regions (UTRs), which modulate the translation efficiency of downstream sequences, were found to negatively affect the association of mRNAs with mitochondria. A mutational approach coupled with in vivo mRNA visualization confirmed this observation. Moreover, this technique allowed the identification of 3'‐UTRs as another essential element for mRNA localization at the mitochondrial surface. Therefore, this work offers new insights into the mechanism, function and regulation of the association of cytosolic mRNAs with plant mitochondria. Significance Statement: We present here a genome‐scale analysis of cytosolic mRNAs targeted to plant mitochondrial surfaces. A major observation is that targeting of mRNAs encoding mitochondrial proteins is strongly correlated with protein function, suggesting a coordinated control of mRNA localization within metabolic pathways. Moreover, upstream AUGs and particular upstream open reading frames (uORFs) in 5' untranslated regions reduce the association of mRNAs with mitochondria. This was confirmed by mRNA imaging, identifying uORFs as potential regulators of mRNA targeting to mitochondria.